Metabolomics approach reveals high energy diet improves the quality and enhances the flavor of black Tibetan sheep meat by altering the composition of rumen microbiota - Zhang, Xue; Han, Lijuan; Hou, Shengzhen; Raza, Sayed Haidar Abbas; Gui, Linsheng; Sun, Shengnan; Wang, Zhiyou; Yang, Baochun; Yuan, Zhenzhen; Simal-Gandara, Jesus; El-Shehawi, Ahmed M.; Alswat, Amal; et al. (Frontiers in Nutrition, 2022)
The current study aims to determine the impact of dietary energy levels on rumen microbial composition and its relationship to the quality of Black Tibetan sheep meat by applying metabolomics and Pearson's correlation analyses. For this purpose, UHPLC-QTOF-MS was used to identify the metabolome, whereas 16S rDNA sequencing was used to detect the rumen microbiota. Eventually, we observed that HS (high energy diet group) improved the carcass quality of Black Tibetan sheep and fat deposition in the longissimus lumborum (LL) compared to MS (medium energy diet group). However, HS considerably increased the texture, water holding capacity (WHC), and volatile flavor of the LL when compared to that of MS and LS (low energy diet group). Metabolomics and correlation analyses revealed that dietary energy levels mainly affected the metabolism of carbohydrates and lipids of the LL, which consequently influenced the content of volatile flavor compounds (VOCs) and fats. Furthermore, HS increased the abundance of Quinella, Ruminococcus 2, (Eubacterium) coprostanoligenes, and Succinivibrionaceae UCG-001, all of which participates in the carbohydrate metabolism in rumen and thus, influences the metabolite levels (stachyose, isomaltose, etc.) in the LL. Overall, a high energy diet is desirable for the production of Black Tibetan sheep mutton because it improves the mouthfeel and flavor of meat by altering the composition of rumen microbiota which influences the metabolism in the LL.